2015
DOI: 10.3390/md13127070
|View full text |Cite
|
Sign up to set email alerts
|

Potential Threats Posed by Tetrodotoxins in UK Waters: Examination of Detection Methodology Used in Their Control

Abstract: Tetrodotoxin is a neurotoxin responsible for many human fatalities, most commonly following the consumption of pufferfish. Whilst the source of the toxin has not been conclusively proven, it is thought to be associated with various species of marine bacteria. Whilst the toxins are well studied in fish and gastropods, in recent years, there have been a number of reports of tetrodotoxin occurring in bivalve shellfish, including those harvested from the UK and other parts of Europe. This paper reviews evidence co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 100 publications
(159 reference statements)
0
16
0
Order By: Relevance
“…Here, confirmation has been provided for the continued presence of TTX, along the south coast of England in particular, between 2014 and 2016 inclusive, confirming the results of the original study were not a one-off event. As such, this study highlights a continued risk to food consumers from TTXs, noting in particular that these toxins are resistant to degradation under food processing conditions such as cooking or freezing [ 19 ]. Overall, the majority of samples analysed contained total TTX concentrations below the 44 µg/kg EFSA guidance threshold [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, confirmation has been provided for the continued presence of TTX, along the south coast of England in particular, between 2014 and 2016 inclusive, confirming the results of the original study were not a one-off event. As such, this study highlights a continued risk to food consumers from TTXs, noting in particular that these toxins are resistant to degradation under food processing conditions such as cooking or freezing [ 19 ]. Overall, the majority of samples analysed contained total TTX concentrations below the 44 µg/kg EFSA guidance threshold [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though most intoxicated people should fully recover usually within 24 h [13], it was also reported that death may occur in less than 30 min [18], indicating a rapid rate of absorption from the gastrointestinal tract. Although hundreds of TTX intoxication cases have been published [19] it is difficult to find a correlation between toxin concentration and poisoning symptoms due to the scarce oral toxicity data. TTX is unequivocally toxic to mammals.…”
Section: Discussionmentioning
confidence: 99%
“…TTX, along with a range of analogues together termed the tetrodotoxins (TTXs) is a low molecular weight, water soluble neurotoxin associated with neurotoxic marine poisonings [ 16 ] found in a wide range of marine phyla, including most famously the pufferfish, as well as gastropods, crustacean, octopus and echinoderms [ 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In recent years it has been detected in bivalve molluscs such as mussels, oysters and clams from the UK [ 36 , 37 ] as well as other parts of Europe including Greece, the Netherlands and Spain [ 38 , 39 ] and also New Zealand [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other marine biotoxins, TTX is associated primarily in the literature with production by bacterial species [ 19 , 41 , 42 , 43 , 44 ], although the biosynthetic pathway for the toxin has not yet been elucidated [ 42 ] and reports proposing association with phytoplankton have also been published for example, [ 30 , 38 ]. Most notable is the co-existence of TTX with certain genera of bacteria, including Vibrio , Bacillus and Pseudomonas [ 35 , 36 , 42 , 43 , 44 ]. The relationship between TTX and Vibrio is especially important given the links between bacterial prevalence, toxin occurrence and climatic change [ 37 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%